The Hermeneutical spiral: a comprehensive introduction to biblical - Osborne, Grant R. (Downers Grove, Ill IVP Academic, 2006)
This comprehensive introduction to biblical interpretation by Grant R. Osborne provides students and pastors with all the necessary tools for moving from sound exegesis to biblical and systematic theology and on to expository preaching.
Homiletics II: the sermon.
Includes bibliographical references and index
Keywords: Bible -- Hermeneutics